Effect of Thiamethoxam on some of Histological and Physiological sides to mice males Reproductive system - نجاح صبر, اسيل (University of Thi-Qar Journal of Science, 2011)
This study refers to role of treatment with doses (0.004,0.08 Mg/ Kg ,B.W.) of incecticide Thiamethoxam for (35) days in induction to make pathological changes in testes tissue of treated mice males and abnormality sperm as well as decreased in sperm concentration and viability sperm percentage ,that was significant (P<0.01) in the second group that treated with high dose